1999
DOI: 10.1557/proc-564-257
|View full text |Cite
|
Sign up to set email alerts
|

Agglomeration Of Cu Electroplating Seed Layers On Ultra-Thin Ta, Ta1-xNx, Tal-xOx, Contaminated Ta, and Composite Ta/Ta1-xNx Diffusion Barriers

Abstract: The agglomeration of thin (10 nm) Cu films suitable for use as electroplating seed layers has been investigated on ultrathin (<4 nm) Ta, Ta1-xNx, Tal-xOx, and composite Ta/Ta1-xNx, diffusion barriers. Copper films on clean 3.6nm Ta barriers deposited by ultrahigh vacuum sputter deposition at up to 120°C are stable against agglomeration during 30 minute anneals at 360°C and display strong (022) crystallographic texture. Similar Cu films deposited on thinner Ta, Ta0 85N0 15, Ta0.95O0 05, and residual gas cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 7 publications
0
7
0
4
Order By: Relevance
“…6͒ and 800°C ͑SEM not shown͒. Comparison of agglomeration behavior for thin-and-thick films has also been reported for Cu ͑15 and 30 nm͒ on SiO 2 , 18 and Pd ͑5 and 50 nm͒ on SiO 2 . 27 Both studies agree that thick films are less easy to agglomerate than thin films after the same heat-treatment.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…6͒ and 800°C ͑SEM not shown͒. Comparison of agglomeration behavior for thin-and-thick films has also been reported for Cu ͑15 and 30 nm͒ on SiO 2 , 18 and Pd ͑5 and 50 nm͒ on SiO 2 . 27 Both studies agree that thick films are less easy to agglomerate than thin films after the same heat-treatment.…”
Section: Resultsmentioning
confidence: 87%
“…In addition, the influence of the copper film thickness on agglomeration was studied also because it has been shown that copper films were less likely to agglomerate when they were relatively thick. 18 The Cu, Ta, and TaN layers were deposited on SiO 2 -covered Si substrates to simulate the interconnection system. The multilayer structures were annealed at various temperatures to examine the agglomeration behavior of copper films.…”
mentioning
confidence: 99%
“…High substrate temperatures were required (no lower than 250 °C for the most reactive precursor Cu­(acac) 2 ). These high substrate temperatures cause agglomeration due the high mobility of copper , at elevated temperatures above 250 °C and can prevent the growth of carbon-free single-phase Cu 2 O …”
Section: Introductionmentioning
confidence: 99%
“…(1) polycrystalline and amorphous Me-N, Me-C, Me-O and Me-B compounds, such as TiN x [25], VN x [26], ZrN x [27], NbN x [28], MoN x [21], HfN x [29], WN x [30], TaN x [31], WC x [32], TaC x [33], MoO x [34], TaO x [35] and TiB 2 [36], (2) polycrystalline and amorphous Me-Si compounds, such as MoSi x [37], WSi x [38] and TaSi x [39], (3) polycrystalline and amorphous Me alloys, such as TiW x [40], TaCo x and TaFe x [41], TaW x [42], NiNb x [43] and CuZr x [44].…”
Section: Metal-based Barriers As Liners For Cu Seed Depositionmentioning
confidence: 99%